(3Odjd UMI GdeOjQjf aj ehGLgI VZhW GdYed hGdMjGI (B/s - (3S(B.(3GdjhJ, O(B.(3QhHQJs; (3EUdGM, CMeO s ((3GdbGgQI(B: s (3eQcR GdNHQGJ GdegfjI ddEOGQI Hejc(B, s, 1998)
(3GdPjf jfaYhf OGFeG ef GdPjf jehJhf ef GdELgGO GdYUHj(B- (3gd JhGLg GdbGJd GdcGef OGNd LSec(B- (3cja jSJLjH LSec ddELgGO GdYUHj(B- (3cd eG jgGLe CLSGefG ef GdNGQL Mhd GdELgGO GdYUHj hGdHjFI(B- (3WH GdELgGO GdYUHj GdLOjO(B- (3JZjQ GdTNUjI hGdYdGL(B- (3eDTQGJ LhOI GdMjGI(B- (3Gdbje NWhI CSGSjI fMh YdGL GdELgGO GdYUHj(B- (3bhI GdEOQGc JQhjV MOjKc eY faSc(B- (3ehGLgI VZhW GdMjGI GdEOGQjI(B- (3EOGQI GdhbJ(B- (3GdJZPjI fMh fXGe ZPGFj UMj hSdje(B- (3GdJeQjfGJ GdHOfjIs
Keywords: (3GdQDSGA hGdeOjQhfs; (3GdQDSGA hGdeOjQhf(B- (3GdUMI GdfaSjIs